Manajemen Stres Berbasis Penulisan Jurnal Emosional: Pengendalian Faktor Risiko Diabetes Melitus - Tati Suryati; Exsos Grend Dais; Maryati Maryati; Ratna Sari Dinaryanti; Sofyan Sofyan; Yanti Riyantini; Muhammad Ali (Universitas Faletehan, 2026)
Diabetes Mellitus (DM) is a chronic disease with a steadily increasing prevalence both globally and nationally. In addition to physical factors, chronic psychological stress plays a significant role in increasing blood glucose levels through metabolic imbalance. However, practical, accessible, and independently applicable stress management interventions are still limited. Emotional journaling has the potential to be a simple, low-cost, non-pharmacological intervention alternative in controlling DM risk factors. This study aims to analyze the effect of emotional journaling-based stress management as a risk factor control measure for DM. The study used a quasi-experimental design with a pre-test and post-test approach without a control group, involving 43 respondents over 18 years of age. The sampling technique used purposive sampling with certain inclusion criteria. The intervention consisted of stress management skills based on emotional journaling, with skills measured using a checklist before and after the intervention. Data analysis was performed using the Wilcoxon signed rank test to determine differences in skills before and after the intervention. The analysis results showed a significant increase in skills after the intervention (p<0.000). These findings confirm that stress management based on emotional journal writing has a positive influence and strategic potential in controlling DM risk factors effectively, easily implemented, at low cost, and sustainably based on community empowerment.